Arcade on second floor gallery - Ghosh, Ayan (Jio Institute, 2023)
FW Stevens submitted two coloured drawings of his design, one of its exterior and one of the Council Chamber, backing it with convincing arguments. He had visited Europe to study town halls and proposed a well-ventilated building for the municipality. Steven's new design was accepted and he was awarded the project, and Chisholm's proposal was cancelled.